Stem rot of eucalyptus cuttings caused by Neopestalotiopsis spp. in Brazil. Issue 6 (9th April 2020) - Santos, Gizeli S.; Mafia, Reginaldo G.; Aguiar, Aurélio M.; Zarpelon, Talyta G.; Damacena, Michelle B.; Barros, Aline F.; Ferreira, Maria A.
Abstract: In Brazil, the fungus Neopestalotiopsis (=  Pestalotiopsis ) is known to cause disease in eucalyptus cuttings. However, although it occurs relatively frequently in cutting nurseries, the pathogenic species have yet to be identified. Thus, the aim of the present work was to perform a morphological and phylogenetic characterization to identify the aetiological agent. For this purpose, the isolates were subjected to a multilocus analysis using the two gene regions β‐tubulin (TUB) and the translation elongation factor (TEF). Based on the genomic sequences, two known species and one new species of the pathogen were identified. After confirmation of their pathogenicity, N. australis was confirmed as a new report in eucalyptus. Neopestalotiopsis rosae failed to differ from the control, however, showed internal and external lesion in eucalyptus stem. In addition, in this study, a new species called N. eucalypti was described, causing disease in hybrids eucalyptus. Morphological characterization allowed for the confirmation of the N. australis and N. rosae isolates, primarily based on differences in the size and shape of the conidia. For N. eucalypti, no morphological marker was found that separated it from the other species within the genus. The results confirm the existence of at least three Neopestalotiopsis species as aetiological agents of leaf spot and stem rot in eucalyptus cuttings in Brazil.